ВЕРБАЛЬНА РЕАЛІЗАЦІЯ ЕМОТИВНОСТІ В АНГЛІЙСЬКІЙ ЛІТЕРАТУРІ ХІХ СТОЛІТТЯ - Цинтар Наталя, Мельничук Роксолана, Симака Анна. (Вісник науки і освіти, 2024)
The article analyzes the linguistic realization of emotions in English literature taking into account the gender of the narrator. Linguistic means of expressing emotivity are divided into two categories: vocabulary that expresses emotions and vocabulary that describes emotions. Vocabulary expressing emotions is analyzed by the following groups: 1) emotives (emotives-addresses, emotive-evaluative vocabulary, interjections); 2) stylistic devices (repetitions, metaphors); 3) syntactic means (emphatic constructions). MAs (male authors) were more likely to use syntactic devices (emphatic constructions), while FAs (female authors) were more likely to use stylistic devices (repetitions, metaphors). Emotives that determine not only the tone (positive or negative) of the emotional state but also its type (joy, pleasure, fear, anger, etc.) are present in almost the same amount both in the MA leterary works and in the FA literary works of the nineteenth century. The group of vocabulary describing emotions includes two groups of verbalizers: individual words – emotives (nouns, adjectives, verbs, adverbs) and lexical constructions that describe facial expressions and gestures during the experience of a certain emotion – kinemes (kinemes of eyes, lips, face, hands). Through the mechanics and motility of the characters' actions, writers seek to highlight the psychological basis of gestures and actions. FA use nouns and adjectives in common compound and compound sentences as well as affectionate addresses. Describing emotional kinemes the focus of the MA is on the eyes while for the FA lip expressions (most often a smile) are the main transmitters of both positive and negative emotions. According to the factor of addressability, which takes into account the type of communication between the addresser and the addressee, we distinguish the authorial, character and complex nomination of the emotional state as in the works of the 19th century.
Keywords: emotivity, emotions, emomotives, kinemes, verbalizers, emphatic constructions, author nomination, character nomination, complex nomination.